(untitled) (Research, Society and Development, 2021)
The interaction between cells and polymeric nanostructures has been considered an important topic for biotechnology. The electrospun fibers present porous structures in the order of submicron with characteristics that mimic the fibrillar components of the natural extracellular matrix, favoring the effective local action of bioactive systems. Complexation of nucleic acids with these fibers and their use in functional recovery and tissue regeneration therapies have been considered alternatives to cell transplantation and inductive protein delivery systems. In customizing the interaction profile between these matrices and the genetic material, it is relevant to maintain the availability of their molecular types in effective concentrations in the microenvironment, with greater gene expression and longer time for therapeutic action. The development of an adequate balance between transfection efficiency and cell viability, different strategies are followed, such as the incorporation of polynucleotides in polymeric solutions or emulsions before the electrospinning process, or even the functionalization of nanofibers by modifying their surface. Because of this, this review aims to present the different methods of producing electrophilic nanofibers functionalized with nucleic acids and their applications in the health area.